Impact of epidermal growth factor receptor gene expression level on clinical outcomes in epidermal growth factor receptor mutant lung adenocarcinoma patients taking first-line epidermal growth factor receptor–tyrosine kinase inhibitors. Issue 3 (March 2017) - Chang, Huang-Chih; Chen, Yu-Mu; Tseng, Chia-Cheng; Huang, Kuo-Tung; Wang, Chin-Chou; Chen, Yung-Che; Lai, Chien-Hao; Fang, Wen-Feng; Kao, Hsu-Ching; Lin, Meng-Chih
Epidermal growth factor receptor (EGFR)-tyrosine kinase inhibitors (TKIs) are first-choice treatments for advanced non-small-cell lung cancer patients harboring EGFR mutations. Although EGFR mutations are strongly predictive of patients' outcomes and their response to treatment with EGFR-TKIs, early failure of first-line therapy with EGFR-TKIs in patients with EGFR mutations is not rare. Besides several clinical factors influencing EGFR-TKI efficacies studied earlier such as the Eastern Cooperative Oncology Group performance status or uncommon mutation, we would like to see whether semi-quantify EGFR mutation gene expression calculated by 2 −ΔΔct was a prognostic factor in EGFR-mutant non-small cell lung cancer patients receiving first-line EGFR-TKIs. This retrospective study reviews 926 lung cancer patients diagnosed from January 2011 to October 2013 at the Kaohsiung Chang Gung Memorial Hospital in Taiwan. Of 224 EGFR-mutant adenocarcinoma patients, 148 patients who had 2 −ΔΔct data were included. The best cutoff values of 2 −ΔΔct for in-frame deletions in exon 19 (19 deletion) and a position 858 substituted from leucine (L) to an arginine (R) in exon 21 (L858R) were determined using receiver operating characteristic curves. Patients were divided into high and low 2 −ΔΔct expression based on the above cutoff level. The best cutoff point of 2 −ΔΔct value of 19 deletion and L858R was 31.1 and 104.7, respectively. In all, 92 (62.1%) patients showed high 2 −ΔΔct expression and 56 patients (37.9%) low 2 −ΔΔct expression. The mean age was 65.6 years. Progression-free survival of 19 deletion mutant patients with low versus high expression level was 17.07 versus 12.04 months (P = 0.004), respectively. Progression-free survival of L858 mutant patients was 13.75 and 7.96 months (P = 0.008), respectively. EGFR-mutant lung adenocarcinoma patients with lower EGFR gene expression had longer progression-free survival duration without interfering overall survival.